Hubungan Timbal Balik Filantropi dan Antropologi - Hanifah, Hana (Department of Anthropology, 2023)
Philanthropic activity is one of the activities that humans have been doing for a long time. It contributes greatly to improving people's welfare, which makes the topic continue to grow. Thanks to the internet, philanthropy has become an icon of the intense dynamic process of social relations that increasingly prominent in today's technological life. Based on the development, this article aims to discuss how the anthropological perspective on philanthropy. With the literature review method, this study shows two things. First, the reciprocal relationship between anthropology and philanthropy that leads to the potentiality of philanthropy as additional project areas for anthropology. Second, the implication related to the urgency of Digital Anthropology to be increasingly considered by anthropologists today as a bridge in studying how people react and communicate with today's digital world.Abstrak: Kegiatan filantropi merupakan salah satu kegiatan yang telah dilakukan manusia sejak lama. Kegiatan ini memberikan kontribusi besar dalam meningkatkan kesejahteraan masyarakat, sehingga topik ini terus berkembang. Berkat internet, filantropi telah menjadi ikon dari proses dinamis yang intens dalam hubungan sosial yang semakin menonjol dalam kehidupan teknologi saat ini. Berdasarkan perkembangan tersebut, artikel ini bertujuan untuk membahas perspektif antropologi tentang filantropi. Dengan metode tinjauan literatur, penelitian ini menunjukkan dua hal. Pertama, hubungan timbal balik antara antropologi dan filantropi yang mengarah pada potensi filantropi sebagai area proyek tambahan untuk antropologi. Kedua, implikasi terkait urgensi Antropologi Digital yang semakin perlu dipertimbangkan oleh ahli antropologi saat ini sebagai jembatan dalam mempelajari bagaimana orang bereaksi dan berkomunikasi dengan dunia digital.